GPR55 in the tumor microenvironment of pancreatic cancer controls tumorigenesis - Ristić, Dušica; Bärnthaler, Thomas; Gruden, Eva; Kienzl, Melanie; Danner, Laura; Herceg, Karolina; Sarsembayeva, Arailym; Kargl, Julia; Schicho, Rudolf (Frontiers in Immunology, 2025)
BackgroundThe G protein-coupled receptor 55 (GPR55) is part of an expanded endocannabinoid system (ECS), and plays a pro-tumorigenic role in different cancer models, including pancreatic cancer. Next to cancer cells, various cells of the immune tumor microenvironment (TME) express receptors of the ECS that critically determine tumor growth. The role of GPR55 in cancer cells has been widely described, but its role in the immune TME is not well understood. MethodsWe intended to uncover the role of GPR55 in tumor immunity in a model of pancreatic ductal adenocarcinoma (PDAC). To this end, a KPCY tumor cell line or a GPR55-overexpressing KPCY cell line (KPCY55) from murine PDAC were subcutaneously injected into wildtype (WT) and GPR55 knockout (KO) mice, and immune cell populations were evaluated by flow cytometry. ResultsDeficiency of GPR55 in the TME led to reduced tumor weight and volume, and altered the immune cell composition of tumors, favoring an anti-tumorigenic environment by increasing the number of CD3+ T cells, particularly CD8+ T cells, and the expression of PDL1 on macrophages. RNA-seq pathway analysis revealed higher T cell activity in KPCY55 tumors of GPR55 KO vs. WT mice. In addition, tumors from GPR55 KO mice displayed increased levels of T cell chemokines Cxcl9 and Cxcl10. Migration of T cells from GPR55 KO mice towards CXCL9 was increased in comparison to T cells from WT mice, suggesting that a CXCR3/CXCL9 axis was involved in T cell influx into tumors of GPR55 KO mice. Notably, anti-PD-1 immunotherapy increased tumor burden in WT mice, while this effect was absent in the GPR55 KO mice. ConclusionOur study indicates that GPR55 in TME cells may drive tumor growth by suppressing T cell functions, such as migration, in a model of PDAC, making it an interesting target for immunotherapies.